Conscious sedation in child patient management - Pil, Adonis T.
Conscious sedation has been defined as a minimally depressed level of consciousness that retains the patients' ability to maintain airwa independently, continuously and respond appropriately to phusical stimulation and verbal command.
This paper presents a report of 104 oral and rectal sedation cases done at the Philippine Children's Medical Center (PCMC), Pediatric Dentistry Division. This represents roughly 5% of the total 2,192 patients treated at the Center during the year 2000-2002. These sedation cases referred both to handicapped and nornal children, indicating the age, as well as sex distribution. Records showed that males are being sedated 2.9 times more than females. Data showed that oral sedation were done more on older children while rectal sedation on younger ones.
Keywords: Conscious sedation; Patient management; Handicapped children; Oral sedation; Rectal sedation